2009
DOI: 10.1111/j.1365-246x.2009.04313.x
|View full text |Cite
|
Sign up to set email alerts
|

High resolutionQ−1estimation based on extension of coda normalization method and its application toP-wave attenuation structure in the aftershock area of the 2005 West Off Fukuoka Prefecture Earthquake (M7.0)

Abstract: S U M M A R YWe developed a method for estimating the seismic-wave attenuation (1/Q) in a seismically active region such as an aftershock area. To estimate the attenuation factor between two adjacent hypocentres, we employed two seismograms recorded at a station and calculate the ratio between two power spectra of direct waves normalized by those in the coda for both the events. The coda normalization of the spectrum and the ratio between the two events minimize the possible influences of sources, sites, instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The spatial distribution of Q in the crust has been drawing attention from seismologists, and a number of studies employing local earthquake tomography techniques to obtain the 3-D distribution of Q have been conducted. 3-D Q tomography is an effective tool for inferring the underground distribution of fracture density and the roles of fluids in the crust (e.g., Rietbrock 2001;Reyners et al 2007;Bennington et al 2008). Matsumoto et al (2009 reported that a high Q P region corresponds to a large-slip fault patch where a large inland shallow earthquake occurred (the 2005 West off-Fukuoka earthquake, Mw 7.0), suggesting a correlation between the frictional strength along the fault and the seismic attenuation of the host rocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution of Q in the crust has been drawing attention from seismologists, and a number of studies employing local earthquake tomography techniques to obtain the 3-D distribution of Q have been conducted. 3-D Q tomography is an effective tool for inferring the underground distribution of fracture density and the roles of fluids in the crust (e.g., Rietbrock 2001;Reyners et al 2007;Bennington et al 2008). Matsumoto et al (2009 reported that a high Q P region corresponds to a large-slip fault patch where a large inland shallow earthquake occurred (the 2005 West off-Fukuoka earthquake, Mw 7.0), suggesting a correlation between the frictional strength along the fault and the seismic attenuation of the host rocks.…”
Section: Discussionmentioning
confidence: 99%
“…In the inversion, we applied a nonnegative least squares method (Lawson and Hanson 1995) because Q −1 P,i cannot take negative values. Note that the first and second integrals (summations) of the observation Equation 5 are evaluated along the ray path from the source at x and along that from the source at x 0 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In these media, we may retrieve P-and S-wave attenuation parameters independently of the site and instrumental transfer functions by using the coda normalization method (Aki and Richards 1980;Yoshimoto et al 1993;Sato et al 2012). In recent years, this method has been applied to S-wave attenuation tomography at local scale, exploiting the strong scattering effects produced by strong heterogeneity in volcanic regions (Del Pezzo et al 2006;Matsumoto et al 2009;Sato et al 2012;De Siena et al 2010). The coda normalization method is based on the equation that correlates the ratio between the S-wave direct energy and the coda wave energy to the spatial distribution of the inverse total quality factors calculated along the source-station ray-path (Del Pezzo et al 2006;De Siena et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic velocity tomography has proven to be a powerful technique to investigate the 3-D crustal and upper mantle structure and seismotectonics [e.g., Zhao et al, 1996;Mishra and Zhao, 2003;Kato et al, 2005;Wang and Zhao, 2006;Wang et al, 2016]. Compared to velocity tomography, seismic attenuation tomography has rarely been applied to large earthquake areas [e.g., Rietbrock, 2001;Matsumoto et al, 2009]. Because seismic attenuation is more sensitive than seismic velocity to some important material properties, such as Journal of Geophysical Research: Solid Earth 10.1002/2016JB013704 temperature, grain size, and water content Toksöz et al, 1979;Jackson et al, 2002;Faul and Jackson, 2005;Aizawa et al, 2008], seismic attenuation tomography is suitable for investigating very heterogeneous regions such as subduction zones [e.g., Eberhart-Phillips and Chadwick, 2002;Schurr et al, 2003;Stachnik et al, 2004;Pozgay et al, 2009;Bohm et al, 2013;Nakajima et al, 2013;Liu et al, 2014;Liu and Zhao, 2015;Saita et al, 2015].…”
mentioning
confidence: 99%